2022
DOI: 10.1161/strokeaha.121.035699
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Therapies for Morbidity and Mortality After Aneurysmal Subarachnoid Hemorrhage: A Systematic Review and Network Meta-Analysis of Randomized Trials

Abstract: Background: Aneurysmal subarachnoid hemorrhage (aSAH) is associated with high mortality and morbidity. We aimed to determine the relative benefits of pharmacological prophylactic treatments in patients with aneurysmal subarachnoid hemorrhage by performing a network meta-analysis of randomized trials. Methods: We searched Medline, Web of Science, Embase, Scopus, ProQuest, and Cochrane Central to February 2020. Pairs of reviewers independently identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 102 publications
1
28
0
Order By: Relevance
“…Cerebral vasospasm and delayed cerebral ischemia (DCI) are major factors for survival and functional outcome following SAH and have, for many years, been the main focus in SAH research [ 42 , 43 , 44 , 45 ]. Clinical parameters such as Hunt and Hess scores, lower modified Fisher grade, the absence of intracerebral hematoma, intact pupillary light reflexes, and clinical improvement before aneurysm treatment can be used as early clinical predictors of functional outcome and favorable/non-favorable prognosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral vasospasm and delayed cerebral ischemia (DCI) are major factors for survival and functional outcome following SAH and have, for many years, been the main focus in SAH research [ 42 , 43 , 44 , 45 ]. Clinical parameters such as Hunt and Hess scores, lower modified Fisher grade, the absence of intracerebral hematoma, intact pupillary light reflexes, and clinical improvement before aneurysm treatment can be used as early clinical predictors of functional outcome and favorable/non-favorable prognosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid hemorrhage is a serious disease with high morbidity and mortality. This disease affects about 30,000 to 40,000 people in the United States and 60,000 people in the world (12)(13)(14). Patients with SAH may suffer from various complications, such as systemic inflammation, myocardial damage, or cardiac dysfunction (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…More than 30% of patients with SAH die within the first days to the first weeks after SAH. Also, if these patients survive, most of them suffer from cognitive disorders or disability (14,21). This disease has significant complications and mortality, and knowing the prognostic predictors and investigating related factors are of special importance.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials designed to treat CAV using mechanical or pharmacological vasodilation have failed to show an improvement in clinical outcome,5 6 and, at this time, oral nimodipine is the only class I and level of evidence A medication that has been shown to be an effective preventative treatment for DCI 7. A recent network metanalysis concluded that nimodipine and cilostazol are likely the most effective treatments in preventing morbidity and mortality in patients with aSAH 8. Interestingly, nimodipine does not reduce CAV, which suggests that this drug more likely inhibits cortical spreading ischemia and has fibrinolytic activity that reduces microthrombi 4 9.…”
Section: Introductionmentioning
confidence: 99%